Influence of surface treatment conditions for organic crystalline scintillators on their scintillation characteristics - Tarasov, V.O.; Andryushchenko, L.A.; Dudnik, O.V.; Rybka, E.A. (Functional Materials, 2018)
The scintillation and optical characteristics of alpha and beta radiation detectors based on organic crystalline scintillators are investigated after the treatment of their surfaces with different compositions. The polishing composition has been matched, which ensures an improvement in the quality of the polished surface and an improvement in the stated characteristics of alpha and beta radiation detectors based on stilbene and activated p-terphenyl single crystals by increasing the light collection coefficient. The parameters of these detectors are retained after exposure to a temperature of +60°C for 12 h. It is also shown that the use of a matched polishing compound makes it possible to obtain a detector of high spectrometric quality based on an activated p-terphenyl single crystal 6×6×6 mm³ in coupling with a SiPM. The energy resolutions for this detector are 5.7, 7.9 and 11.9 % when electrons of internal conversion with energies of 1048, 976 and 554 keV are being registered.